(untitled) (Research, Society and Development, 2021)
Allium sativum L. is a flavoring with a characteristic flavor and phytochemical composition rich in active ingredients with antimicrobial activity. This study aimed to evaluate the antifungal potential in vitro of the aqueous extract of A. sativum against pathogenic fungi isolated from the soil. Thirty soil samples were collected in three public squares in the city of Maceió - Al and then processed for the isolation of fungi using the soil suspension technique. Fungi were identified by visualizing the macroscopic and microscopic aspects of the colonies. The aqueous extract of A. sativum (AE) was obtained through infusion of the fragmented bulb and the antifungal susceptibility tests were performed through agar diffusion. As a result, 256 Colony Forming Units (UFC) were obtained, of which 110 (42.9%) corresponded to Aspergillus sp., 52 (20.3%) Mycelia sterilia, 28 (10.9%) Penicillium sp. and 24 (9.4%) Beauveria bassiana. In relation to AE, it showed antifungal activity against Beauveria bassiana, Aspergillus sp. and Penicillium sp., exhibiting inhibition halos that varied from 10 to 30 mm. These findings demonstrate the antifungal activity of garlic against different fungi from the soil, which is related to its rich phytochemical composition that provides direct fungicidal action and acts in the inhibition of the mycelium and in the germination of the spores.